Confiabilidad y validez del cuestionario de apoyo social en pacientes con cáncer de Trujillo - Baca R., Deyvi (2016)
The research was aimed analyze the validity and reliability of the MOS Social Support Sherbourne and Stewart (1991) to patients with cancer in Trujillo. Study instrumental. The simple consisted of 100 patients diagnosed with cancer, aged 18 and both sexes. The instrument used was the Questionnaire MOS Perceived Social Support (MOS), developed by Sherbourne and Stewart (1991), and a data sheet designed for the study purposes. The techniques used were Cronbach’s alpha for reliability and exploratory factor analysis (EFA) of principal axes for validity. The results achieved a high level of reliability (